2017
DOI: 10.30958/aje.4-4-3
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into a Whole School Experience: The Implementation of Teaching Teams to Support Learning and Teaching

Abstract: This paper presents some of the emerging outcomes from the experiences of a Maltese school that decided to embrace the philosophy of inclusion using a whole school approach based on the social model of disability. This was a qualitative study based on focus groups. A thematic analysis was used within an interpretative approach of hermeneutic phenomenology. Most schools in Malta now include 'inclusive' settings. This entails the use of a class Learning Support Assistant who is assigned to one or more classes wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The findings of this study robustly demonstrate that the implementation of the whole school approach yields substantial improvements in the educational quality of the 408 schools within the Thai educational landscape. This positive outcome resonates with previous research conducted by Ferrante (2017), Mogren et al (2019), and Katikas and Sotiriou (2023), who also identified the beneficial impact of the whole school approach in diverse contexts. These collective findings underline the broad applicability of this approach and its potential to enhance educational quality across various settings.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings of this study robustly demonstrate that the implementation of the whole school approach yields substantial improvements in the educational quality of the 408 schools within the Thai educational landscape. This positive outcome resonates with previous research conducted by Ferrante (2017), Mogren et al (2019), and Katikas and Sotiriou (2023), who also identified the beneficial impact of the whole school approach in diverse contexts. These collective findings underline the broad applicability of this approach and its potential to enhance educational quality across various settings.…”
Section: Discussionsupporting
confidence: 88%
“…Employing a survey involving 256 teachers, their findings demonstrated that schools employing the whole school approach managed their educational processes differently, ultimately resulting in more favorable educational outcomes. Ferrante (2017) explored the consequences of implementing a comprehensive school approach within the framework of inclusion, with a specific focus on disabled students and the social model of disability. Utilizing focus groups and thematic analysis within a framework of hermeneutic phenomenology, Ferrante's qualitative exploration centered on a Maltese school's adoption of the approach.…”
Section: Previous Whole School Projectmentioning
confidence: 99%
“…These relate closely to the improvement of teaching quality in inclusive classrooms (Sokal & Sharma, 2017). Moreover, according to many researchers, it is essential to encourage open debates and discussions in the workplace, among teaching staff (Ferrante, 2017), about all the challenges they face in the daily routine of working with SEN children. Open debates can be the starting point for teachers to enable the learning environments, by feeling free to express their questions and ask for help, and share the best experiences and skills (Tedam, 2013), so they can solve their challenges (Gash, 2006).…”
Section: Professional Development (Pd) Of Teachers Regarding Inclusiv...mentioning
confidence: 99%